Zonated Copper‐Driven Breast Cancer Progression Countered by a Copper‐Depleting Nanoagent for Immune and Metabolic Reprogramming - Lin Chen; Saibo Ma; Hao Wu; Lingna Zheng; Yunpeng Yi; Guangnian Liu; Baoyi Li; Jiayi Sun; Yang Du; Bing Wang; Yike Liu; Cheng Zhang; et al. (Advanced Science)
Abstract While studies of various carcinomas have reported aberrant metal metabolism, much remains unknown regarding their spatial accumulation and regulatory impacts in tumors. Here, elevated copper levels are detected in breast cancer tumors from patients and animal models, specifically exhibiting a zonate spatial pattern. Spatially resolved multiomics analyses reveal that copper zonation drives a tumor metabolic preference for oxidative phosphorylation (OXPHOS) over glycolysis and promotes tumor metastatic and immune‐desert phenotypes. Then, a copper‐depleting nanoagent is developed based on copper chelator tetrathiomolybdate (TM)‐loaded hybridized bacterial outer membrane vesicles (hOMVs) from both Akkermansia muciniphila bacteria and CD326‐targeting peptide‐engineered Escherichia coli (TM@CD326hOMV). Systemic administration of TM@CD326hOMV reduces the labile copper level in tumors and inhibits both tumor growth and metastatic phenotypes, specifically through metabolic reprograming of OXPHOS toward glycolysis and restoration of antitumor immunity responses involving natural killer cells, CD4+ T cells, and cytotoxic CD8+ T cells in tumors. Assessing survival in murine breast cancer models, a combination of TM@CD326hOMV and a checkpoint blockade agent outperforms monotherapies. Notably, a copper‐rich diet undermines the therapeutic efficacy of TM@CD326hOMV. Beyond demonstrating an effective nanoagent for treating breast cancer, this study deepens the understanding of how the pattern of copper accumulation in tumors affects pathophysiology and immunity.